Keterbukaan Diri ODHA (Orang dengan HIV/AIDS) terhadap Pasangannya dalam Menghadapi Stigma Masyarakat - Gracia Kristianus, Stella; Pudjo Santoso, Hedi (Interaksi Online, 2019)
HIV / AIDS have become a phenomenon in the social environment of society for the last few years. Even though the number of people living with HIV / AIDS continues to increase, people's knowledge of HIV / AIDS itself is still very low. Fear of stigma and discrimination from local people makes PLWHAs reluctant to reveal themselves. This study aims to explain how PLWHA open up to their partners in the midst of negative stigma from the society, specifically to find out how PLWHA open themselves to their partners so that they can make big decisions in establishing a more serious relationship into the marriage level. The method that’s being used is a qualitative approach with case studies. Social Penetration, Labelling Theory and Johari Windows will be used to see this phenomenon. The data collection is done by conducting in-depth interviews with informants. Subjects in this study were couples of PLWHA who had established relationships in marriage for some time, who were selected purposively and based on the willingness of the informants to share. In this study it was found that personal closeness will affect the self-disclosure of PLWHA to others. Spouse will usually be the only place to open up and share stories with because they have undergone social penetration to a more intimate stage. So that PLWHAs dare to open themselves up and make big decisions to get to the marriage level.